Artificial intelligence in education: A systematic mapping study using Scopus and Web of Science - Maran Chanthiran; Abu Bakar Ibrahim; Mohd Hishamuddin Abdul Rahman; Punithavili Mariappan (Pejabat Karang Mengarang UPSI, 2022)
Education in the 21st century is beginning to adopt the use of artificial intelligence, which is a type of technology. Through a search of the Scopus and the Web of Science databases, the primary objective of this methodical investigation is to locate publications that have been subjected to the rigors of peer review and are associated with the field of artificial intelligence in education. Additionally, analyze current trends and challenges in applying artificial intelligence in education. A bibliometric survey of the application of artificial intelligence in educational settings is also analyzed in further detail here. For the purpose of gaining access to the relevant literature, the Scopus and Web of Science databases were utilized. Utilizing the more advanced keyword search capabilities of the VOS viewer software along with the PRISMA methodology. The sample for the study consisted of a total of 298 articles and studies were analyzed between the years 2014 and 2020. According to the results of a bibliometric study, there are ten researchers who stand out as the primary scholars contributing to the field of artificial intelligence technology in education. An examination of the relevant literature reveals that there is a requirement for the development of software and applications of artificial intelligence in education, specifically those that are able to generate graphics from the text that has been loaded. Education has the potential to be a significant driver of advancement in natural language processing within artificial intelligence.